THREE NEW SPECIES OF DIXELLA DYAR & SHANNON (DIPTERA: DIXIDAE) FROM SANTA CATARINA, BRAZIL - Corrêa, Caio Cezar Dias; Scarpa, Priscila Luiza; Pinho, Luiz Carlos; Gil-Azevedo, Leonardo Henrique (Zootaxa, 2024)
We describe three new species of Dixella Dyar & Shannon: Dixella moultoni sp. nov., Dixella jailtoi sp. nov., and Dixella spinosa sp. nov., and record Dixella limai (Santos, 1940) and Dixella trinitensis (Lane, 1943) from the state of Santa Catarina, Brazil. The new species can be distinguished by coloration of the thorax and morphology of the male and female terminalia (except Dixella jailtoi, the female of which is unknown). This represents the first record of Dixidae for Santa Catarina, as well as for the Southern Region of Brazil. An identification key as well as distribution map for these species are provided.